2005
DOI: 10.1111/j.1365-2966.2005.09041.x
|View full text |Cite
|
Sign up to set email alerts
|

On model predictions of the power spectral density of radial solar p modes

Abstract: We investigate the frequency dependence of the power spectral density of low‐degree solar p modes by comparing measurements with the results of a stochastic‐excitation model. In the past it was common practice to use the total power in such investigations. Using the maximum of the power spectral density instead provides a direct comparison with the measured mode heights in the observed power spectrum. This method permits a more careful calibration of the adjustable parameters in the excitation model, a model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
195
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(214 citation statements)
references
References 30 publications
18
195
1
Order By: Relevance
“…A detailed derivation of the solution can be found in Samadi & Goupil (2001, SG herefater) or in Chaplin et al (2005). We recall below the main steps.…”
Section: The Inhomogeneous Wave Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed derivation of the solution can be found in Samadi & Goupil (2001, SG herefater) or in Chaplin et al (2005). We recall below the main steps.…”
Section: The Inhomogeneous Wave Equationmentioning
confidence: 99%
“…As an alternative to comparing theoretical results and observational data, Chaplin et al (2005) proposed to derive H from the theoretical excitation rates, P, and the observed mode line width, Γ , according to the relation:…”
Section: Seismic Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldreich and Keeley 1977;Balmforth 1992;Houdek et al 1999;Chaplin et al 2005;Belkacem et al 2008;Houdek 2010). We refer to stars exhibiting such an oscillation pattern as solar-type stars hereafter.…”
Section: New Asteroseismic Diagnostics Of Global Stellar Convection mentioning
confidence: 99%
“…Goldreich and Keeley 1977;Balmforth 1992;Houdek et al 1999;Chaplin et al 2005;Belkacem et al 2008). The first observations of granulation are quite old (Herschel 1801), but it is not until 1933 that their turbulent origin was unveiled (Siedentopf 1933).…”
Section: Stellar Convection and The Background Signal In Oscillation mentioning
confidence: 99%